Adaptation Mechanisms of Company Operation: How the Business Survived in the Depressive Region in the Beginning of 2000s - РыжоваНаталья Петровна (Journal of Economic Sociology, 2010)
The paper is an attempt to study the phenomenon of company’s adaptation and institutional changes. The main distinctive feature of the paper is the discussed spatial situation of the firm: all the objects of our study operate in the border region of Amurskaya oblast. The paper consists of 6 parts. The first part contains the theoretical concepts and research schemes, the second part describes the results of the existed research review devoted to the companies of 1990s-2000s. the third part is focused on the description of the institutional and economic characteristics of the Amurskaya oblast that influence the adaptation mechanisms of the companies. The fourth part shortly characterizes the methodology of the empirical study and the fifth part provides the results of the study. The last one is devoted to the discussion of the perspectives of firms’ development in the region and the possibilities of usage of the paper results.